Validation of GOME ozone profiles by means of the ALOMAR ozone lidar - G. Hansen; K. Bramstedt; V. Rozanov; M. Weber; J. P. Burrows (Annales Geophysicae, 2003)
Ozone vertical profiles derived from nadir measurements of the GOME instrument on board the ERS-2 satellite, by means of the FURM algorithm of the University of Bremen, are validated against measurements with the stratospheric ozone lidar at the ALOMAR facility in North-Norway. A set of 43 measurements, taken in the period August 1996 to September 1999 with a maximum distance between the ground-based site and the GOME pixel centre of 650 km, is used. The comparison shows a satisfactory agreement within less than ± 7% in the altitude range 15 to 30 km, independent of the season of the year. At lower altitudes, average deviations of the GOME profiles from lidar measurements of up to - 15% occur in spring, the reason for which has to be found in the FURM algorithm, while the agreement is within ± 5% in both winter and summer/autumn months. At altitudes above 30 km, significant seasonally varying discrepancies occur, being largest in winter ( - 40% on average at 40 km altitude) and smallest in summer (less than - 10%). The source of these deviations is most likely related to a radiance and irradiance calibration problem in the GOME data below 300 nm, which are used to derive ozone at the highest altitudes. The validation also shows that it is very important to choose the right ozone climatology for initialisation. Satisfactory results in spring 1997, when the polar stratospheric vortex was very stable, are only achieved, if a winter (vortex) profile is used. Key words. Atmospheric composition and structure (middle atmosphere-composition and chemistry; instruments and techniques; general or miscellaneous)